ANALISIS NIAT MAHASISWA BERWIRAUSAHA - Winata, Andri (Jurnal Manajemen Magister Darmajaya, 2016)
The purpose of this study was to determine the influence of the IbK incentive towards the intention to entrepreneurship of IIB Darmajaya students. This research is a quantitative study with the associative method. Associative research is research that aims to study the relationship between the variables of the study. Secondary data were obtained from requesting database of samples studied, while the primary data obtained through questionnaires. The results showed that the IbK incentive had no influence toward the intention to entrepreneurship at student of IIB Darmajaya.Keyword: Incentives IBK, Intention to entrepreneurship